(Re‐)Designing Nature? An Overview and Outlook on the Ethical and Societal Challenges in Synthetic Biology. Issue 6 (7th May 2019) - Braun, Matthias; Fernau, Sandra; Dabrock, Peter
Abstract: This structured literature analysis aims to map the current, emerging, and predicted future of synthetic biology (SB) by putting the focus on the implied conceptual, societal, and ethical challenges. The central objective of the analysis is to provide an initial systematization of the ethical and socio‐scientific debate on SB by structuring and categorizing widely discussed issues within the debate in recent years. Starting with the quest for possible definitions, issues of biosafety and biosecurity are emphasized. Furthermore, the focus is on the more conceptual challenges of SB, including the relationship between natural and synthetic, or concepts of life and living. From the very beginning, one specific characteristic of SB has been a strong entanglement with different forms of public participation. In some respects SB has already taken a leading position in claiming and orchestrating itself as an integrative and participatory discipline. After addressing SB as an emerging biotechnology at the interface between science and society, a venture is initiated to focus on the possible regulatory and governmental challenges which are entangled in SB. Abstract : This structured literature analysis aims to map the current, emerging, and predicted future of synthetic biology (SB) by focusing on the implied conceptual, societal, and ethical challenges and emphasizing the issues of biosafety and biosecurity. Furthermore, the more conceptual challenges of SB, including the relationship between natural and synthetic, or concepts of life and living, are introduced and discussed.